2005
DOI: 10.2337/diabetes.54.7.2179
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents High-Glucose–Induced Endothelial Cell Death Through a Mitochondrial Permeability Transition-Dependent Process

Abstract: Hyperglycemia-induced oxidative stress is detrimental for endothelial cells, contributing to the vascular complications of diabetes. The mitochondrial permeability transition pore (PTP) is an oxidative stress-sensitive channel involved in cell death; therefore, we have examined its potential role in endothelial cells exposed to oxidative stress or high glucose level. Metformin, an antihyperglycemic agent used in type 2 diabetes, was also investigated because it inhibits PTP opening in transformed cell lines. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
175
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(199 citation statements)
references
References 40 publications
15
175
1
8
Order By: Relevance
“…An et al (2006) showed that metformin reduces highfat-induced cardiac cell death, through inhibition of ceramide synthesis. Similarly, metformin was shown to prevent high glucose-induced endothelial cell death (Detaille et al, 2005). This discrepancy suggests that even though they both activate the AMPK pathway, AICAR and metformin mediate their effects through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al (2006) showed that metformin reduces highfat-induced cardiac cell death, through inhibition of ceramide synthesis. Similarly, metformin was shown to prevent high glucose-induced endothelial cell death (Detaille et al, 2005). This discrepancy suggests that even though they both activate the AMPK pathway, AICAR and metformin mediate their effects through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…AICAR is known to induce apoptosis while metformin was shown to protect endothelial cells from apoptosis (Detaille et al, 2005;Kim et al, 2007). LNCaP cells were incubated with metformin, AICAR and staurosporine as a control.…”
Section: Metformin Does Not Induce Apoptosismentioning
confidence: 99%
“…The LDH data suggest that the increase in expression of Hsp60 observed at both mRNA and protein levels were not due to cellular lysis and that the growth inhibitory effects of 500 μM metformin was not due to cell death but possibly due to metformin having an inhibitory effect on mitochondrial bionenergetic functions. Interestingly, metformin has been documented to prevent cell death by modulation of the mitochondrial permeability transition pore opening induced by a glutathione-oxidising agent t-butyl hydroperoxide (Guigas et al 2004) and also due to high glucose-induced cell death in a human dermal microvascular endothelial cell line, HMEC-1 (Detaille et al 2005). However, reports of metformin treatment resulting in an increase in H 2 O 2 production in rat liver mitochondria (Carvalho et al 2008), a short-term trial involving 15 type 2 diabetes mellitus patients treated with metformin showing an elevation in oxidative stress, indicated by elevated malidialdehyde levels (Škrha et al 2007) and metformin causing mitochondrial depolarization and oxidative stressdependent apoptosis in cultured glioma cells (Isakovic et al 2007), suggest that the role of mitochondria in metformininduced cytotoxicity remains to be of defined.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has also been shown that metformin inhibits mitochondrial complex I activity leading to the impairment of mitochondrial function [5][6][7]. However, it has also been shown that metformin prevents the mitochondrial permeability transition pore (PTP) opening in both permeabilized and intact KB cells [8], and in permeabilized human microvascular endothelial cells (HMEC-1) [9]. In opposition, Isakovic et al [10] reported that metformin acts as a PTP inducer in C6 rat glioma cell line.…”
Section: Introductionmentioning
confidence: 92%